Indigenous people in Aotearoa New Zealand are overrepresented in cannabis convictions - Wetini Rapana; Taylor Winter; Ririwai Fox; Benjamin C. Riordan; Rajas Kulkarni; Waikaremoana Waitoki; Damian Scarf (BMC, 2022)
Abstract Background Previous work has demonstrated that cannabis laws have had a disproportionate impact on Māori, the Indigenous people of Aotearoa New Zealand. In 2019, the New Zealand Government amended cannabis laws, providing police with the power to determine whether a therapeutic or health-centred approach would be more beneficial than a conviction. In the current study, we use population level data to assess whether this law change has ameliorated the bias in cannabis convictions for Māori. Methods Data were drawn from the Integrated Data Infrastructure (IDI), a large government database hosted by Aotearoa New Zealand's national statistics office. In the IDI, we selected individuals who (1) were between 18 and 65, (2) were Māori or Pākehā (New Zealanders of European descent) and, (3) had any cannabis charges that proceeded to the courts. Results Māori ethnicity was a significant predictor of the odds of receiving a cannabis conviction for Māori males (Odds: 1.56), with a marginally significant effect for Māori females (Odds: 1.57). Further, for Māori, there was no reduction in the number of cannabis charges before vs. after the amendment to cannabis laws. Conclusion The current study demonstrates that the bias in cannabis convictions for Māori remain. Given this, the New Zealand Government must follow other countries around the world and move forward on cannabis law reform.